Could Basel Regulatory Framework Have Saved Lebanese Banks? - Khalil Feghali; Dolly Wajih Mikhael; Hiyam Sujud (Universitas Trisakti, 2021)
This paper aims to enhance in-depth analysis of the impact of various risks: credit risk, interest rate risk, market risk and liquidity risk as well as the volume of activity on the capital adequacy ratio of the Lebanese banks. It is confined to 31 banks out of the 63 banks operating in Lebanon, non-probability sample, during the period 2012-2018 using the regression analysis. The findings indicate that all the independent variables have a negative impact on banks’ solvency; while the liquidity risk has a positive effect, the market risk and the volume of activity variables have no significant relationship with the solvency of banks. Meanwhile, credit risk has proven its largest and most important role in the ability to reduce or increase the Lebanese banks’ solvency. But banks still have to respect a liquidity ratio, which is confirmed by the Basel III agreements. The originality of this study comes from the particularity of Lebanese banks for its core role in the Lebanese economy. This research is the first attempt that models the relationship between the above stated variables and the capital adequacy ratio; especially in the pre-crisis period, that Lebanon went through, which immediately led to the liquidity shortage crisis.